I need help finding the derivative of

(x^2+sinx)secx

3 answers

let y = (x^2 + sinx)/cosx

by quotient rule....
dy/dx = ( cosx(2x + cosx) - sinx(x^2 + cosx) )/cos^2 x

simplify if needed.
there is no quotient it is multiplication
I changed secx to 1/cosx

however, if you insist on using the product rule

dy/dx = (x^2 + sinx)(tan^2 x) + (2x + cosx)(secx)

illustrating that there is often more than one way to express the same result.
Similar Questions
  1. What is a simplified form of the expression [sec^2x-1]/[(sinx)(secx)]?a. cot x b. csc x c. tan x***** d. sec x tan x I think
    1. answers icon 2 answers
  2. how do i simplify (secx - cosx) / sinx?i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i
    1. answers icon 1 answer
  3. Prove the following:[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
    1. answers icon 3 answers
  4. My previous question:Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
    1. answers icon 2 answers
more similar questions